Healing synchrony? potential benefits of interpersonal synchrony for chronic pain management - Świdrak, Justyna (Frontiers in Pain Research, 2025)
Fibromyalgia is called a pathology of misconnection at the neurophysiological, psychological, and social levels, and is characterised by widespread musculoskeletal pain, which is accompanied by a series of symptoms, such as chronic fatigue, depression, anxiety, body perception disturbances, and cognitive deficits. In this article, I argue that interventions that in various ways enhance interpersonal neural synchronisation (INS) may bring long-term benefits to people with fibromyalgia (PwF). In the first part, I briefly introduce studies on INS in the general population. In the second part, I hypothesise that interpersonal synchrony may contribute to symptom reduction for individuals with fibromyalgia, in the sense that repeated experience of being in sync with others may play a role in restoring both the brain-body and self-others connection in this population and consequently result in simultaneous lasting improvement of wellbeing. In the final part, I discuss potential future research directions.